Gas/Substrate Fluxes and Microbial Community in Phenol Biodegradation Using an O2-Based Membrane Biofilm Reactor - Hanay, Ozge; Taskan, Ergin; Yildiz, Burcin; Hasar, Halil; Casey, Eoin (Wiley, 2014)
[Abstract Not Available]
Keywords: Waste-Water; Removal; Kinetics; Denitrification; Degradation; Wastewaters; Performance